Open Journal System: Assistance and training in submitting scientific journals to be well-indexed in Google Scholar - Triono, Triono; Darmayanti, Rani; Saputra, Nopa Dwi; Afifah, Ani; Makwana, Gautam (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2023)
The technical issue with current human resources is that they still require writing instruction. When Google has published and indexed the manuscript, another problem is incorrectly registering the title, author's name, journal name, pages, and other identification information. Modern technology influences the methods and applications of each open journal system (OJS). Understanding how to submit a manuscript to OJS from the outset is important. The service seeks to improve Google Scholar's indexing of scientific journal submissions to OJS by enhancing their comprehension. The method for implementing the service comprises three stages: preparation, implementation, and evaluation. Based on the activity results, it is evident that participants are enthusiastic and motivated to participate in the training because the knowledge garnered from this training will assist them in completing assignments to publish journals, works, final reports, dissertations, and PKM.